IMPLEMENTASI KEBIJAKAN BADAN USAHA MILIK DESA (BUMDES) DALAM PENGEMBANGAN DESA WISATA (STUDI PADA BUMDES SAMBIMADU, DESA SAMBIBULU, KECAMATAN TAMAN, KABUPATEN SIDOARJO) - Nurul Maulidiah; Suci Megawati (Universitas Negeri Surabaya, 2022)
BUMDes policy is based on Law No. 6 of 2016 and Permendesa PDTT No. 4 of 2015 on Establishment, Management, Management and Dissolution of BUMDes. BUMDes Sambibulu is one of the BUMDes in Sidoarjo Regency which was established in 2018. The purpose of the research is to find out and analyze thesuccess rate of bumdes policy implementation process run by BUMDes Sambimadu in developing tourism villages through agrotourism development. This type of research is descriptive with an qualitative approach. The focus of research is on the success rate of bumdes policy implementation process in the development of tourism villages. The research subjects consisted of the Head of Sambibulu Village, Chairman of BUMDes Sambimadu, Bumdes Employee and Sambibulu Village Community. Technique data collection uses observation, interviews, and documentation. This technique is data collection, data reduction, data presentation, and with drawing conclusions. The results of study show that the implementation of BUMDes policy in the development of Tourism Village has not been fully successful because the Human Resources owned by BUMDes Sambimadu are still inadequate and competent, characteristics shown by BUMDes employees busy with their respective affairs so that they take their duties and responsibilities. Cognition skills that do not fully understand the policy of BUMDes Sambimadu in the development of Tourism Village. On the other hand, there is support from good communication between the village government and BUMDes Sambimadu because every week it evaluates activities to correct existing deficiencies in the BUMDes policy implementation process. Keywords: Policy Implementation, BUMDes, Tourism Villages.